Police leadership and administration: a 21st-century strategic approach - Vito, Gennaro F. (Routledge, 2025)
"This innovative text adapts the strategic management process to the police organizational environment, illustrating how to tailor responses to the unique problems and issues that professionals are likely to face in the field of law enforcement. The authors cover pioneering management techniques for leaders facing the challenges of today's complex environment, offering police executives guidance on planning, setting direction, developing strategy, assessing internal and external environments, creating learning organizations, and managing and evaluating the change process. The book also tackles how to handle the political, economic, social, and technical considerations that differ from one community to the next. Providing a foundation with which to adapt to an ever-changing criminal justice climate, this book trains leaders to search for solutions, rather than relying on old formulas and scientific management principles. It is an essential resource for forward-thinking police leadership courses in colleges and professional training programs"--